Analisis Hasil Uji PMT 150kV Pada Gardu Induk Cilegon Baru BAY KS 1 - Didik Aribowo (Universitas Negeri Padang, 2019)
In this modern era, the need for electricity has become a primary need in both big cities and small cities, almost all of our daily life support equipment requires electrical energy. PLN as the only company engaged in the distribution of electrical energy researches in the field of maintenance, especially testing of PMT insulation prisoners. Based on IEV (International Electrotechnical Vocabulary) 441-14-20 stated that Circuit Breaker (CB) is a mechanical switching / switching equipment, which is able to close, drain and break the load current under normal conditions and is able to close, drain ( within a certain time period) and break the load current under specific abnormal conditions / disturbances such as short circuits. to be used as material for the PMT analysis. The minimum PMT isolation resistance limit at the operating temperature is calculated